2000
DOI: 10.1243/0954411001535660
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral contact forces

Abstract: Glenohumeral contact forces have only been calculated previously either for simple abduction or for athletic activities. The objective of this study was to determine the glenohumeral contact forces for tasks which are demanding of the shoulder but which would commonly be performed by older people. The functional tasks chosen were using the arms to stand up from and sit down into a chair, walking with a cane, lifting a 5 kg box to shoulder height with both hands, and lifting a 10 kg suitcase. The trunk angles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 25 publications
4
51
2
1
Order By: Relevance
“…Muscular forces as well as total contact forces calculated with the model were low compared to values found in the literature [4,6,7,33]. The difference may be explained by the different motions considered.…”
Section: Discussioncontrasting
confidence: 59%
“…Muscular forces as well as total contact forces calculated with the model were low compared to values found in the literature [4,6,7,33]. The difference may be explained by the different motions considered.…”
Section: Discussioncontrasting
confidence: 59%
“…This confirms that the posterior area is loaded more intensely than the anterior or central regions. All these results concur with the regional variations reported for the material properties, such as bone density or strength [27][28][29][30], and the mechanical characteristics, such as loading conditions on the glenoid [34,13,22]. This suggests that an analysis of the morphological and mechanical characteristics of the trabecular bone would help to predict the predominant loading placed on the glenoid.…”
Section: Discussionsupporting
confidence: 86%
“…Results from additional models indicated that this material behavior did not affect joint kinematics. A compressive 1-kN load is in the in the upper bound of expected glenoid loading, 35 and so was used in all analyses of constraint and conformity. The magnitude of shear loading required to induce joint instability was calculated for each of the seven constraints (Fig.…”
Section: Constraintmentioning
confidence: 99%